2014
DOI: 10.1177/1066896914541001
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thyroid Tissue in the Adrenal Gland

Abstract: Foci of ectopic thyroid tissue are uncommon. Most sites of thyroid ectopia are confined to the neck region. The presence of ectopic thyroid tissue outside the migration pathway of the primitive thyroid in other locations is exceptional. Given that any disease of the thyroid gland may also affect ectopic thyroid tissue, pathologists has to recognize benign or malignant conditions that may develop in the ectopic focus. We present the case of a 32-year-old woman with ectopic thyroid parenchyma in the adrenal glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
8
1
5
Order By: Relevance
“…Clinical reports of extra-lingual ectopic thyroid tissue are rare. We found a few studies of ectopic thyroid in adrenal gland (4,5), gallbladder (6), jejunum (7) and mesentery (8) but not pure ectopic thyroid in the breast. The etiology of this abnormality is not fully understood.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical reports of extra-lingual ectopic thyroid tissue are rare. We found a few studies of ectopic thyroid in adrenal gland (4,5), gallbladder (6), jejunum (7) and mesentery (8) but not pure ectopic thyroid in the breast. The etiology of this abnormality is not fully understood.…”
Section: Discussionmentioning
confidence: 94%
“…Guerra et al [4] reported that adrenal gland thyroid is very rare and is di cult to understand based on thyroid embryology. However, on the basis of the reported cases [5][6][7][8][9][10][11][12][13][14], the adrenal gland is not an uncommon site of abdominal ET. The cause of adrenal gland ET remains unknown.…”
Section: Adrenal Gland Etmentioning
confidence: 99%
“…Localizaciones mas distantes del trayecto normal de migración han sido reportados, como el esófago, ovario, corazón. Estas localizaciones son menos frecuentes [6][7][8][9] . Se ha reportado un solo caso de localización axilar.…”
Section: Discusionunclassified
“…En nuestro caso, se trataba de un nódulo bien delimitado, sin atipias celulares correspondiente a una lesión benigna. Una metástasis, un cancer tiroideo 9 o una transformación maligna del tejido tiroideo ectópico, raramente descrito como carcinoma papilar y folicular [11][12][13] , fueron excluidos.…”
Section: Discusionunclassified
See 1 more Smart Citation